Protein carbonylation as a possible way to modulate breast cancer cell proliferation - E. V. Shakhristova; E. A. Stepovaya; A. A. Sadykova; V. V. Novitsky (Сибирский онкологический журнал)
Introduction. High rates of cancer incidence and mortality worldwide dictate the necessity of developing new methodological approaches in understanding the molecular mechanisms of cancer progression associated with intracellular redox regulation imbalance.The objective of the study was to evaluate the role of protein carbonylation in regulating breast cancer cell proliferation under redox status modulation.Materials and Methods. In the intact breast cancer cells and in the cells cultured under redox status modulation using 5mM N-ethylmaleimide (an - SH group blocker) and 5 Mm 1,4-dithioerythritol (a thiol group protector), the concentration of thioredoxin and its carbonylated form was measured using Western blot analysis. The activity of thioredoxin reductase and the level of protein carbonyl derivatives were determined using spectrophotometry. Cell cycle phase distribution was evaluated by flow cytometry.Results and Discussion. Under the effect of N-ethylmaleimide, cell cycle arrest in the S-phase was confirmed by oxidative modification of proteins, including thioredoxin carbonylation. When culturing MCF-7 cells in the presence of 1,4-dithioerythritol, cell cycle arrest in the G0/G1 phases was associated with a rise in the concentrations of reduced thioredoxin and glutathione forms.Conclusion. The thioredoxin system and oxidative modification of proteins are involved in redox-dependent modulation of breast cancer cell proliferation. Studies in the area of redox proteomics offer great potential to seek molecular targets of malignant transformation of breast cells.